RhoA activation during polarization and cytokinesis of the early Caenorhabditis elegans embryo is differentially dependent on NOP-1 and CYK-4 - Yu Chung Tse; Michael E. Werner; Katrina M Longhini; Jean‐Claude Labbé; Bob Goldstein; Michael Glotzer (2012)
The GTPase RhoA is a central regulator of cellular contractility in a wide variety of biological processes. During these events, RhoA is activated by guanine nucleotide exchange factors (GEFs). These molecules are highly regulated to ensure that RhoA activation occurs at the proper time and place. During cytokinesis, RhoA is activated by the RhoGEF ECT-2. In human cells, ECT-2 activity requires its association with CYK-4, which is a component of the centralspindlin complex. In contrast, in early Caenorhabditis elegans embryos, not all ECT-2-dependent functions require CYK-4. In this study, we identify a novel protein, NOP-1, that functions in parallel with CYK-4 to promote RhoA activation. We use mutations in nop-1 and cyk-4 to dissect cytokinesis and cell polarization. NOP-1 makes a significant, albeit largely redundant, contribution to cytokinesis. In contrast, NOP-1 is required for the preponderance of RhoA activation during the establishment phase of polarization.